Revisiting the Impact of ICT to the Tourism Development - Iris Mihajlović; Ivan Strugar (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Technological development and tourism is close connected since exponential growth is realized in both areas in last 50 years. Information and communication technology influence on global scale on tourism development, and tourism development change the business practice and development strategies. Three new systems has dramatically influence on tactical and strategic level of doing business, computer reservation systems, global distribution system and Internet. Technological changes are obvious in three directions: radical changes in existing industries, development of new industries, incentive of new market development and industries which are not in direct connection with new technologies. The aim of this paper is to point on new technologies development on tourism thru overview of previous research.
Keywords: L83; O31; 330; tourism; ICT; technology; innovation